Compliance with Iron Tablet Consumption and the Risk of Anemia in Third Trimester Pregnant Women in the Context of Midwifery Communication - Yuliwati Yuliwati; Siti Maisaroh (Universitas Pahlawan Tuanku Tambusai, 2026)
Anemia in third trimester pregnant women remains a common health issue and has the potential to increase the risk of pregnancy complications. Iron tablet consumption is one of the preventive measures for anemia, but the level of compliance among pregnant women in consuming them varies, influenced by individual characteristics, knowledge levels, and midwifery communication processes during antenatal care. This study aims to analyze iron tablet consumption compliance and the risk of anemia in third-trimester pregnant women in the context of midwifery communication in the working area of the